Prevalence of Musculoskeletal Pain and Its Association with Computer Workstation Ergonomics among Undergraduates in Malaysia - Kong, Yi Ling; Ong, Jun Hui (INTI International University, 2023)
Background: Advanced technology promotes students to utilize computers widely for educational purposes, leading to increased musculoskeletal (MSK) pain among undergraduates. This study aimed to identify the prevalence of various MSK pain and its association with computer workstation ergonomics among undergraduates in Malaysia. Method: A cross-sectional study was conducted using a self-administered online questionnaire among 390 undergraduates. Data on Nordic Musculoskeletal Questionnaire and Computer Workstation Checklist were collected. Descriptive statistics were used to evaluate the prevalence of MSK pain and its association with computer workstation ergonomics was analysed using the chi-square test. Results: 79.1% and 52.7% of the participants reported MSK pain in the past 12 months and 7 days respectively. This study also revealed that pain in the neck, elbow, wrist, lower back, hip, knee, and ankle in the past 12 months were associated with the computer workstation ergonomics, namely the height of the armrest, keyboard, and input device, monitor’s viewing distance and level, the usage of a comfortable keyboard, comfortable input device and document holder, with p<0.05. Whilst pain in the neck, wrist, and knee in the past 7 days were associated with the chair seat width, monitor’s distance and height, obstruction under the table, and usage of document holder, with p<0.05. Conclusion: This study revealed that more than half of the undergraduates have experienced MSK pain and there is an association with computer workstation ergonomics. Therefore, undergraduates should be educated on the proper computer workstation ergonomics as a preventive measure for MSK pain.